2010
DOI: 10.3233/wor-2010-0983
|View full text |Cite
|
Sign up to set email alerts
|

Changes in posture: A case study of a dental hygienist's use of magnification loupes

Abstract: Evidence suggests that using magnification loupes will improve the posture of dental clinicians, thus decreasing work-related musculoskeletal disorders. The purpose of this case study was to document the experiences of a dental hygienist during a four week acclimatization period. Methods: Documentation was comprised of self-reports from the dental hygienist's reflective journaling and postural measurements made by a trained observer using Branson's Posture Assessment Instrument (BPAI), a validated posture asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 4 publications
1
22
1
Order By: Relevance
“…We found the prevalence of pain was significantly higher among dentist who worked in non-ergonomic environment, used therapeutic chairs without lumbar support and armrests. It is well established that use of ergonomically designed equipment reduce muscular load and fatigue during work and can reduce risk of developing WMSDs [16,18,19]. On the contrary, the results from this study pointed out that previous knowledge about WMSDs was not well disseminated and implemented in a daily dental work.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…We found the prevalence of pain was significantly higher among dentist who worked in non-ergonomic environment, used therapeutic chairs without lumbar support and armrests. It is well established that use of ergonomically designed equipment reduce muscular load and fatigue during work and can reduce risk of developing WMSDs [16,18,19]. On the contrary, the results from this study pointed out that previous knowledge about WMSDs was not well disseminated and implemented in a daily dental work.…”
Section: Discussioncontrasting
confidence: 58%
“…Nowadays, use of the optical devices such as loupes and microscopes has increased in the dental profession which are associated with less awkward postures and decreased level of the static muscle load work in different work positions [18,19]. Interestingly, there are only a few studies conducted to assess preventive measures for reducing work-related MS pain in dentistry.…”
Section: Attempts To Combat Ms Painmentioning
confidence: 99%
“…Serval studies have discussed specific ergonomic risk factors and preventive measures in the dentistry field . However, among the students that participated in the present study only 14% reported that they received ergonomic education, and the numbers were higher among the experienced dental hygienists but were still relatively low (40%).…”
Section: Discussionmentioning
confidence: 99%
“…Loupes are an eyewear system of telescopes attached to lenses ( Fig. 1), which magnify the viewing field; in the case of dental clinicians, this means the teeth and the gingiva [24]. However, there appears to be no longitudinal studies or research using objective measures to support this innovation.…”
Section: Loupes As a Preventive Measure Against Msdmentioning
confidence: 99%
“…Current research into the effect of loupes appears to have been limited to self-reported measures of MSD through the use of questionnaires [18,27,28], or a single case study reporting a student's experiences [24]. To our knowledge, there is no contemporary research in the literature that has utilised triangulation methods to assess the effectiveness of using loupes on MSD in practising dental hygienists.…”
Section: Loupes As a Preventive Measure Against Msdmentioning
confidence: 99%